The Predicament of the Immigrant Victim/Defendant: VAWA Diversion and Other Considerations in Support of Battered Women - Harris, Zelda B. (2003)
While the struggle to combat domestic violence has made many gains over the last thirty years, some low-income women of color have been left behind. Mandatory misdemeanor domestic violence prosecution policies are periodically used against the victims of domestic violence. Particularly in the case of immigrant victim/defendants, arrest, prosecution, or conviction for a domestic violence misdemeanor at the command of rigid mandatory arrest and prosecution laws can result in significant unintended consequences, including increasing a batterer's power and control over the victim. This article examines those consequences in the context of southern Arizona. Discretionary prosecution policies, referral to immigration and legal assistance, and community education could mitigate the harms of mandatory arrest procedures that burden victims